Synthesis and Characterization of Chitosan Nanoaggregates from Gladius of Uroteuthis duvauceli - Anusha, J. R.; Fleming, Albin T. (International Journal of Biomaterials, 2016)
We report the synthesis, characterization, and biological properties of chitosan nanoaggregates from gladius of squid, Uroteuthis duvauceli. β-Chitin extracted from gladius was deacetylated to chitosan and further reduced to nanosize using ionic gelation process. The morphology and occurrence of chitosan nanoaggregates (CSNA) were observed using transmission electron microscopy (TEM). The degree of deacetylation (DD%) calculated from Fourier transform infrared (FTIR) spectrum showed high value (~94 ± 1.25%) for chitosan. The CSNA depicts low molecular weight, stable positive zeta potential, and less ash and moisture content with high water and fat binding capacity. The antimicrobial activity was tested against pathogenic microorganisms, which depicted significant rate of inhibition against Staphylococcus aureus and Escherichia coli due to high cellular uptake. The antioxidant analysis for CSNA demonstrated high reducing power and scavenging activity towards superoxide radicals compared with the commercially available chitosan. Furthermore, nanoaggregates exhibited low cytotoxic behavior in biological in vitro tests performed using cervical cancer cell line. These results indicate that chitosan nanoaggregates synthesized from waste gladius will be highly efficient and safe candidate for biological applications as food packing film, drug carrier, and tissue engineering.